Cancer Risk Assessment and the Biostatistical Revolution of the 1970s-A Reflection - Kenny Crump (SAGE Publishing, 2018)
Before around 1960, assessment of risk from exposure to toxic substances, including risk of cancer, was generally implemented using the NOAEL-safety factor approach that essentially assumed that an exposure threshold existed and exposures below the threshold carried no risk. In the 1970s there came a realization that cancer could develop from a mutation in a single cell and consequently it was unlikely that a threshold existed for substances that could cause such mutations, and that risk could increase linearly with exposure. During this time the Environmental Protection Agency (EPA) was formed and charged with protecting the public from a perceived high risk of environmental cancer. Faced with this difficult task, EPA decided to assess cancer risk by fitting a statistical model to dose-response cancer data and extrapolating to low dose using the fitted model. After some early experimentation EPA selected the Linearized Multistage Model for this fitting, which predicted risk increased linearly with exposure at low exposures. This approach led to an increased emphasis on statistical issues in risk assessment. Today, cancer risk assessment guidelines allow for different approaches depending upon the understanding of a substance's mode of action. However, a review of EPA's experience with current guidelines indicates that most cancer risk assessments still follow procedures similar to those initiated more than 40 years ago.